KOTA YOGYAKARTA DAN BEBERAPA KOTA PENDAHULUNYA - Inajati Adrisijanti (Berkala Arkeologi, 1998)
In discussing Yogyakarta in terms of urban archeology, it should not be separated from the ancient cities around it, because the city of Yogyakarta is one of the chains of development of cities in Java, especially in the interior. As is known, the capital of the Mataram-Islam kingdom was first in Kota Gede. This first capital functioned until the death of Sultan Agung. Then his successor, namely Susuhunan Amangkurat I, moved the capital to Plered until he escaped from the palace which was then occupied by Trunajaya. In 1680 Susuhunan Amangkurat II founded the city of Kartasura which functioned until 1745, when Susuhunan Pakubuwana II moved to Surakarta.